Utilization of Data Mining Techniques in SIMPUS towards Smart Library at IAIN Kendari - Samrin; Badarwan; Raehang; Obaid Moh. Yahya; Syahrul (E3S Web of Conferences)
The use of data mining techniques in the Library Management Information System (SIMPUS) has great potential to support the transformation of conventional libraries into Smart Libraries. This study aims to analyze the application of data mining techniques in SIMPUS at IAIN Kendari, in order to improve the efficiency of library management and provide smarter services to users. By using algorithms such as association rules, clustering, and classification, historical data on borrowing and collection management can be processed to produce valuable insights, such as user behavior patterns, book need predictions, and collection recommendations. This research uses a quantitative approach with a descriptive exploratory design. The results of the study indicate that the implementation of data mining techniques can improve the quality of library services, facilitate strategic decision making, and provide a more personalized experience to users. This study concludes that the integration of data mining in SIMPUS is a strategic step to support the digitalization and modernization of technology-based libraries at IAIN Kendari.